Activity and stability optimization of RuₓIr₁₋ₓO₂ nanocatalyst for the oxygen evolution reaction by tuning the synthetic process - Nguyen, Tam Duy (2022)
IrO2 and RuO2 are known as two of the best catalysts for the oxygen evolution reaction (OER) in acidic electrolyte. It is reported that RuO2 has higher OER catalytic activity, while IrO2 possesses better electrochemical stability during the OER process in acid. Therefore, many combined strategies have been proposed to utilize the advantages of both IrO2 and RuO2 catalysts in water electrolysis applications. In this article we describe how, by tuning the wet-chemical synthesis process in which the Ir precursor is added after the synthesis of RuO2 nanoparticles (NPs) (two-step), the Ru0.5Ir0.5O2 NPs have been synthesized to improve the OER catalytic activity in both acidic and alkaline media. In detail, the specific OER activity of the Ru0.5Ir0.5O2 NPs (with a particle size of ca. 10 nm) is 48.9 μA cm−2 at an overpotential ŋ = 0.22 V (vs. RHE) and 21.7 μA cm−2 at ŋ = 0.27 V (vs. RHE) in 0.1 M HClO4 and 0.1 M KOH, respectively. These values are higher than those for the one-step (Ir0.5+Ru0.5)O2 NPs (obtained by contemporaneously adding both Ru and Ir precursors), which are 19.5 and 15.5 μA cm−2 at the same measuring conditions, respectively. Additionally, with more IrO2 component distributed on the particle surface, the two-step Ru0.5Ir0.5O2 NPs show better OER catalytic stability than RuO2 NPs.